DETERMINAN PERILAKU TERHADAP PENGGUNAAN ANTIBIOTIK PADA BALITA DI WILAYAH KERJA PUSKESMAS KUBU II KARANGASEM - Ida Ayu Nyoman Trijayanti Ida Ayu Nyoman Trijayanti; iwan saka nugraha; Putu Melista Putri Putu Melista Putri (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Introduction: Antibiotics are recognized as crucial therapeutic compounds in the prevention and management of infections, especially in the pediatric population. In Indonesia, infectious diseases persist as the leading contributors to both morbidity and mortality in children under five, triggering an urgent need for quick and efficient medical interventions. In clinical practice, antibiotics are often chosen as the primary response by parents and medical personnel due to their perceived instant effectiveness. However, the use of antibiotics without proper scientific and policy considerations have the capacity to induce enduring negative consequences, affecting not only individuals but also reverberating across global scale. Objective: This research’s objective is to elaborate the influence of occupation, knowledge, education level, gender, age, and perception on the behavior of Antibiotic use behavior in toddlers at Public Health Center whose working areas are in Kubu II. Method: This study used a cross-sectional quantitative study method. This study has a population of parents of toddlers aged 0 to 59 months in Tianyar Tengah Village whose working area is in Kubu II, totaling 186 participants. Results: This research reveals that some predictors such as occupation, educational attainment, knowledge, and perception play a crucial role in shaping antibiotic usage patterns among children under five. While gender and age did unsignificantly affected. The educational level emerges as the most significant predictor influencing antibiotic usage patterns in children under five. Conclusion: Education level was the most influential predictor of antibiotic use in under-fives.